PERAN ORANG TUA DALAM MENGANTISIPASI PENGARUH NARKOBA PADA REMAJA DI DESA BAJIMINASA KECAMATAN GANTARANGKEKE KABUPATEN BANTAENG (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This research raises the main problem of "How the Role of Parents in Anticipating Drug Use in Adolescents in Bajiminasa Village, Gantarangkeke District, Bantaeng Regency, with subproblems, namely: How are parents' efforts to anticipate the influence of drugs on adolescents in Bajiminasa Village, Gantarangkeke District, Bantaeng Regency? and what factors become obstacles and support in anticipating the influence of drugs on adolescents in Bajiminasa Village, Gantarangkeke District, Bantaeng Regency? The results of this study indicate that, the efforts made by parents in anticipating the influence of drugs on adolescents, namely: first creating closeness and communication, parents building closeness and communication so that children can be more open if they have problems. The supporting and inhibiting factors for parents in anticipating the influence of drugs on adolescents in Bajiminasa Village are supporting factors: providing positive activities for adolescents, namely religious activities and sports activities. Inhibiting factors: environmental factors, disharmonious family conditions, lack of supervision.